MODELLING AND EXPERIMENTAL INVESTIGATION OF MICROEXPLOSIONS IN FUEL DROPLETS - NISSAR, ZUHAIB (2020)
A new analytical solution to the one-dimensional transient heat conduction equation in a composite spherically symmetric water-fuel emulsion droplet, suspended in a hot gas, is obtained. Two solutions to the problem based on the boundary condition at the droplet surface are considered. In the first case, the droplet is subject to the Dirichlet boundary condition at the surface and continuity conditions at the fuel-water interface. The surface temperature is assumed to be constant at all times and evaporation is ignored. In the second case, the Robin boundary condition at the surface of a droplet and continuity conditions at the fuel-water interface are used. In both cases, a water sub-droplet is assumed to be located at the centre of a fuel droplet, the radius of which was fixed at each time step; it could change at the next time step. The Abramzon and Sirignano model is applied for the analysis of the droplet evaporation process. The new analytical solution and the evaporation model are incorporated into a numerical code in which droplet heating/evaporation and the variable thermophysical properties are accounted for. The time instant at which the temperature at the fuel-water interface becames equal to the boiling temperature of water is identified with the initiation of puffing, giving rise to microexplosion.